PEMETAAN RAGAM HIAS ACEH DALAM KAJIAN GEOGRAFI BUDAYA DAN ETNOGRAFI - T. Junaidi; Mufti Riyani (Jurnal Koridor, 2018)
Ornament is a symbol of cultural identity in a society that is in tune with the essence as homo symbolicus. The process spawned a culture in the development of decoration that is specific typical by region or culture. This study intends to acquire mapping in order to facilitate the identification of decorative ornamentation Acehnese, because in creative economy industry appears uniform and does not address the real wealth Aceh. Mapping the typical decorative loacl region these cultures can be analyzed based on the study of geographical and ethnographic analysis that refers to a system of understanding of space and time which embraced the people of Aceh. This study utilizes ethnographic methods to move select projects ethnography, collecting ethnographic data, creation of ethnographic recordings, analysis and writing ethnography. The result showed that the outline of decorative Aceh can be divided into pattern Aceh East Coast, West Coast and Interior Styling Aceh. This study is expected to be the conservation of the wealth of decorative Aceh so can be used in a variety of media culture in the future.